The The Absence of Legal Recognition and Its Impact on the Living Conditions of Urban Pakistani Refugees in Bangkok - Jesper Kulvmann (Journal of Southeast Asian Human Rights, 2017)
Recently, an increasing number of refugees originating from non-neighbouring countries have arrived in Bangkok seeking asylum at UNHCR. As Thailand does not recognize their refugee status and by so their human rights guaranteed in the Declarations of Human Rights, this group of people, referred to as urban refugees, remain in Bangkok illegally during the application process and until possible resettlement. This study examines how restrictions of their human rights, such as absent of fear of arrest, right to work, access to proper housing, education and health provisions, and a prolonged application process affect the physical and mental health of urban refugees. Data are gathered from semi-structured interviews of 53 Pakistani refugees and officers at organisations working with refugees. Depression and declining physical health are common complains while refugee children fail to enrol in formal education. Considering the lack of support for a human rights dialogue in the Thai society it is recommended that a more pragmatic approach, not employing a human rights narrative, is applied to promote the living conditions for urban refugees living in Bangkok.